Building MPLS Network Simulation Using GNS3 at PT. Telkom - Apsari, Ratih; Rosmiati, Mia; Zani, Tafta (International Journal of Engineering and Technology, 2019)
The Backbone Network of PT Telkom Indonesia ( PT.Telkom) has architecture from core layer to access layer. In the core layer network PT Telkom has two stage, there are Main pop and Primary pop. This paper proposed MPLS ( Multiprotocol Label Switching) for core layer to optimize the network. The principle of MPLS ( Multiprotocol Label Switching ) Network  is labelling MPLS to 2nd header layer and 3rd layer for easier checking the network. By using Graphical Network Simulator (GNS3), PT Telkom can simulate its Network using MPLS and calculate the Quality of Service (QoS). From Wireshark’s  summary, the parameter of  QoS when uploading and downloading data process can be captured. In this research, the packet loss has 0% and if it compared with ITU-T category for packet loss, the proposed network achieved good category.  Therefore the proposed method can be be used as an alternative for Telkom’s backbone network in the future.